Management accounting in Portuguese hotel enterprises : the influence of organizational and cultural factors - Santos, Luís Lima (2015)
Nowadays the increase in competition within the hotel and lodging industry is becoming more notorious. Management accounting has evolved in order to respond to the increasing challenges imposed by the management and the competitive economy. So, the interest in management accounting within the lodging industry is growing and it is considered useful to support the decision making process. In the literature, there may be found several studies that refer determinants that influence management accounting, supported by the contingency theory. Contingency theories of management accounting have produced new results. Analyzing the contingency theory from a functionalism perspective, management accounting is influenced by external environment, technology, organization structure, organization size, organization strategy and national culture. The present research project has selected as object of study the hotels in Portugal. We opted for the development of a questionnaire at several hotels. The data was subjected to statistical analysis. This study as the objective of characterizing management accounting in the Portuguese lodging industry, particularly in hotels, identifying the techniques adopted, the deepness of their use, the degree of satisfaction of management with these techniques and their adequacy for the decision-making process, understand the extent to which the industry adopts and use the Uniform System of Accounts for the Lodging Industry (USALI) and identify the factors that influence management accounting. In relation to this last point, we used contingency theory to examine if there are some factors that influence the Portuguese hotels in its management accounting. We focused our study on the organizational structure and culture factors. According to the results obtained, we have concluded that management accounting in hotel and lodging industry is essentially to make decision and to prepare budgets. Management accounting in Portuguese hotels provides adequate information to hotel managers and it is influenced by factors supported by the contingency theory.